Analisis Penggunaan Umpatan pada Konten YouTube Milyhya Berjudul Voice to all 2.0, Test Panci 2.0, Epic Chicken Dinner - Maguna Eliastuti; Rosita Triani; Eka Rachmawati; Inayah Sukmawati; Audry Jesica Meilani; Martina Dos Santos DE Aroju (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Swearing is part of the communication contained in a language. Swearing in its use is a form of expression that comes from anger or resentment towards something. However, the use of swearing has grown over time, swearing is not only used to express anger, but can also be used to express surprise, admiration or intimacy with other people. This research was conducted with the aim of examining the swearing that was said on Milyhya's YouTube content entitled, voice to all 2.0, Test Pot 2.0, Epic Chicken Dinner. The method used in this research is a case study in descriptive qualitative. The research data was taken from video conversations on Milyhya's YouTube account which contained swear words. The method used in data collection is through data collection techniques through searching data and documentation. The results showed that there were 16 data where the 16 swear words consisted of 5 basic words, 1 derived word, 4 phrases and 5 sentences. The swearing data that the researcher found included 2 types of meaning, namely connotative meaning and referential meaning. The referential meaning is divided into several functions, namely the emotive function and the poetic function.